Impact of common ALDH2 inactivating mutation and alcohol consumption on Alzheimer’s disease - Seike, Takuya; Chen, Che-Hong; Mochly-Rosen, Daria (Frontiers in Aging Neuroscience, 2023)
Aldehyde dehydrogenase 2 (ALDH2) is an enzyme found in the mitochondrial matrix that plays a central role in alcohol and aldehyde metabolism. A common ALDH2 polymorphism in East Asians descent (called ALDH2*2 or E504K missense variant, SNP ID: rs671), present in approximately 8% of the world's population, has been associated with a variety of diseases. Recent meta-analyses support the relationship between this ALDH2 polymorphism and Alzheimer's disease (AD). And AD-like pathology observed in ALDH2 -/-null mice and ALDH2*2 overexpressing transgenic mice indicate that ALDH2 deficiency plays an important role in the pathogenesis of AD.Recently, the worldwide increase in alcohol consumption has drawn attention to the relationship between heavy alcohol consumption and AD. Of potential clinical significance, chronic administration of alcohol in ALDH2*2/*2 knock-in mice exacerbates the pathogenesis of AD-like symptoms.Therefore, ALDH2 polymorphism and alcohol consumption likely play an important role in the onset and progression of AD. Here, we review the data on the relationship between ALDH2 polymorphism, alcohol, and AD, and summarize what is currently known about the role of the common ALDH2 inactivating mutation, ALDH2*2, and alcohol in the onset and progression of AD.